Price Indexes for Elementary Aggregates Derived from Behavioral Assumptions - John K. Dagsvik; Leif Brubakk (Statistics Norway, Research Department, 1998)
This paper discusses the properties of price- and Cost-of-Living indexes that follow from specific assumptions about the structure of consumer preferences. Of particular interest are indexes for elementary aggregates. In the first part of the paper we show how particular indexes for elementary aggregates emerge from a micro model with heterogeneous consumers and unobservable choice sets of product variants. Subsequently, we demonstrate that these indexes also follow from a particular preference structure of a representative consumer. Indexes that are currently used in many countries emerge as special cases of the ones proposed in this paper.
Keywords: C43; 330; Elementary aggregates; Price indexes; Cost-of-Living indexes; Price aggregation